ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PADA PEMERINTAH KOTA MEDAN - Manurung, Amran; Fau, Sinarihati (Jurnal Manajemen dan Bisnis, 2014)
The purpose of this research is to know the factors effect the quality of financial statement information on city government Medan. Based on the government regulation number 71 of 2010, the quality of financial statement information of central and regional government must fulfill qualitative characteristic. The factors are researched such as the competency of human resources, the system of internal contol, and the use of information technology The collecting data are done by giving questioner to 40 respondents which are SKPD staff.at the agency of regional financial management on city government Medan. All questioners are returned completely. The data are analized by using SPSS. The result of this research showed that significant value > 0,05 and it can be concluded that the variable of human resources did not have significant effect to the quality of financial statement information. And the significant value < 0,05 and it can be concluded that the system of internal control and the use of information technology has significant effect to the quality of financial statement. Based on F-test, the significant value < 0,05 and F-count > F-table and can be concluded that the variable of human resourses, the system of internal control and the use of information technology has positive effect simultenously to the quality of financial statement.